Perempuan Dalam Representasi Iklan Yang Berperspektif Gender - Rahmah, Wahyuni Shifatur (Musawa Jurnal Studi Gender dan Islam, 2007)
Reconstructing women to obtain a role equal to that of men requires cognizance on how to deconstruct the dominant ideology of the patriarch. As representation plays as a mean of legitimating or preserving ideology and social phenomenon, women should be put forward taking roles traditionally accomplished my men. This is not an easy task however, because at the end actual representation ultimately reflects social culture.